Ocean Remote Sensing Based on Radar, Sonar and Optical Techniques (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
At present, radar, sonar and optical techniques are often applied in ocean remote sensing. Radar is typically used above the ocean’s surface, while sonar and optical technologies are exploited below the surface. Given the increasing application of these three techniques in the field, this reprint mainly focuses on ocean remote sensing based on radar, sonar and optical methods. It discusses a wide range of topics, which can be divided into three groups. The first group includes five papers that primarily explore the direction of arrival (DOA) and radar signal processing. Through this method, rapid and accurate DOA estimation results are provided. The second group, consisting of ten papers, addresses underwater acoustic image and signal processing, which is challenging due to complications in the underwater environment such as bottom reverberation, spatial–temporal structures, noise, and dynamic underwater flow fields, among others. The last group, represented by one paper, concentrates on underwater optical image enhancement and assessment.